2023
DOI: 10.1038/s41598-023-28107-z
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil composition and total phenolic content in Cupressus arizonica G. in response to microbial inoculation under water stress conditions

Abstract: Arizona Cypress is one of the drought-resistant, aromatic, and aesthetically pleasing trees having several pharmacological uses. Certain microorganisms contribute to the secondary metabolism and synthesis of bioactive compounds in aromatic and medicinal plants. This study aimed to determine the photosynthetic pigments, total phenolic content, antioxidant capacity, and essential oil composition of Arizona cypress under two irrigation regimes and microbial inoculations. We established a factorial experiment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
(61 reference statements)
2
7
0
Order By: Relevance
“…Qian et al (2023) reported higher saponin VI accumulation in Paris polyphylla when inoculated with Rhizophagus irregularis in water-deficit condition. Similarly, greater carotenoid content was observed in mycorrhizal Brassica juncea, Lactuca sativa, and Cupressus arizonica (Srivastava et al 2022;Ouhaddou et al 2022;Aalipour et al 2023). In addition, Funneliformis mosseae colonization improved coumarin, phenolic compounds, and flavonoids in Olea europaea, Poncirus trifoliata, and Mentha piperita (Tekaya et al 2022;Ostadi et al 2023).…”
Section: Maintenance Of Ros Levelmentioning
confidence: 82%
“…Qian et al (2023) reported higher saponin VI accumulation in Paris polyphylla when inoculated with Rhizophagus irregularis in water-deficit condition. Similarly, greater carotenoid content was observed in mycorrhizal Brassica juncea, Lactuca sativa, and Cupressus arizonica (Srivastava et al 2022;Ouhaddou et al 2022;Aalipour et al 2023). In addition, Funneliformis mosseae colonization improved coumarin, phenolic compounds, and flavonoids in Olea europaea, Poncirus trifoliata, and Mentha piperita (Tekaya et al 2022;Ostadi et al 2023).…”
Section: Maintenance Of Ros Levelmentioning
confidence: 82%
“…This suggests that microbial inoculation reduces the impact of drought on wheat. In a similar study, an AMF substantially increased the chlorophyll and carotenoid content of Cupressus arizonica (Aalipour et al 2023) Vesicle formation was more in microbial inoculated as compared to uninoculated plants. Vesicle formation increases under stress conditions (Karim et al 2014).…”
Section: Discussionmentioning
confidence: 68%
“…and P. brutia Ten. ( Deligöz and Cankara, 2020 ), and Cupressus arizonica G. ( Aalipour et al., 2023 ). This study also revealed that resistant genotypes have higher levels of carotenoids and chlorophyll ( Table 3 ), which likely contributed to a more effective defensive system that preserves higher visual quality ( Table 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids have a protective impact against oxidative stress, contribute to chlorophyll detoxification, and mitigate the toxicity of free radicals ( Zhang et al., 2021 ). Plants with a higher carotenoid content have a more effective defense against reactive oxygen species and exhibit greater water stress tolerance ( Noctor et al., 2016 ; Aalipour et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%